Upaya Meningkatkan Keaktiafan Siswa Dalam Pembelajaran Akuntansi Dengan Metode Problem Based Learning Pada Siswa Kelas 2 SMAN 1 Toroh - Sholikhin, Riyadzus (2016)
The purpose of this study was to describe the increase in activity of students in the subjects accounting methods Problem Based Learning in Class 2 student at SMAN 1 Toroh. This study includes classroom action research with qualitative descriptive study design. Collecting data in this study was the observation, documentation, and testing techniques. Data analysis technique used is the comparative analysis and analysis kritis.Hasil analysis of this research is to increase keakaktifan students in subjects accounting methods Problem Based Learning in Class 2 student at SMAN 1 Toroh concluded that the average value of pre test in the first cycle is 50.63 and the average value of post test on the first cycle is 63.7. Then increase the value of post-test and post-test cycle I cycle II, find the average value of post test on the first cycle is 63.7 and the average value of post test on the first cycle is 68. Increased activity of students in cycle 1 were moderate with a score 2 to 3.Terutama activity of students in asking students and teachers, student This is due to less familiar accounting jurnal.Pada primarily in the manufacturing activity of reading material and a discussion with the teacher appears that students are also less can be active, it is also due their lack of understanding of the material, so students only rely on friends who are good when discussing it. Increased activity of students in the second cycle lies in the task of student learning, discussions with friends and teachers and also the task of the practice. The most visible is in the activity of the student asked the teacher and other students. This is because the implementation of Problem Based Learning method is well done and the approach of teachers to students is done every cycle, so that students feel helped and not awkward to ask and active.